Cultivation of solidarity and soft power: Ukrainian President Zelensky’s 2022 speech to Japan - Matsuoka, Misato; Matsuoka, Rieko (Lesya Ukrainka Eastern European National University, 2022)
Words not only describe the world but also influence the world or modify relationships (Austin, 1965; Pinker et al,, 2008). Since Russia’s invasion of Ukraine in February 2022, Ukrainian President Volodymyr Zelensky has presented his competence in influencing or even shaping diplomatic relationships through his words and utterances. This study explores the ways in which he has been successful as a strategic speaker (Lee & Pinker, 2010), establishing solidarity with Japan using the soft power introduced by Nye (2004, 2011). By closely examining his 12-minute online speech at the Japanese parliament in March 2022, it investigates the extent to which his speech has exerted influence on the Japanese people as well as on the two countries’ relationship. As for methodology, the data of an English-translated script were analyzed by adopting politeness theory (Brown & Levinson, 1987), which stems from the concept of “face” (Goffman, 1967), a positive social value in social interaction. Specifically, all of President Zelensky’s utterances were evaluated by three factors that account for politeness strategies – relative power, social distance, and weight of imposition. Based on this analysis and the responses in Japan, this study argues that his speech adopted not only face-threatening but also face-boosting effects (Bayraktaroğlu, 1991), building common ground as an affiliation strategy and generating solidarity and soft power. This study concludes that President Zelensky’s speech to Japan contributes to consolidating solidarity in Japanese minds and soft power, which have encouraged the Japanese government and its citizens to continue supporting Ukraine financially, psychologically, and diplomatically.
Keywords: Zelensky’s speech; politeness theory; face; common ground; solidarity; soft power; speech act of request